Rattus xanthurus - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Rattus xanthurus (Gray, 1867). Proc. Zool. Soc. Lond., 1867:598. TYPE LOCALITY: Indonesia, NE Sulawesi, Tondano, 3600 ft. DISTRIBUTION: Sulawesi; northern arm, central core, and SE peninsula. Absent from the SW peninsula where it is replaced by R. foramineus in coastal lowlands and R. bontanus on Gunung Lampobatang. Occurs sympatrically with R. marmosurus on the NE Peninsula. SYNONYMS: faberi, facetus, orientalis, paraxanthus, salocco (see Musser, 1971c-e, 1984). COMMENTS: Member of the group which includes R. bontanus, R. foramineus, R. marmosurus, and R. pelurus. Sody (1941) included xanthurus in Taeromys. Although the R. xanthurus group may eventually be removed from Rattus (Musser and Holden, 1991), it does not belong in Taeromys. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 662, DOI: 10.5281/zenodo.7353098